Woven EndoBridge Embolized Aneurysm Clippings: 2-Dimensional Operative Video. Issue 4 (25th June 2021) - Heiferman, Daniel M; Peterson, Jeremy C; Johnson, Kendrick D; Nguyen, Vincent N; Dornbos, David; Moore, Kenneth A; Inoa, Violiza; Hoit, Daniel A; Arthur, Adam S
Abstract: The Woven EndoBridge (WEB) device (MicroVention, Aliso Viejo, California) is an intrasaccular flow disruptor used for the treatment of both unruptured and ruptured intracranial aneurysms. WEB has been shown to have 54% complete and 85% adequate aneurysm occlusion rates at 1-yr follow-up. 1 Residual and recurrent ruptured aneurysms have been shown to have a higher risk of re-rupture than completely occluded aneurysms. 2 With increased utilization of WEB in the United States, optimizing treatment strategies of residual aneurysms previously treated with the WEB device is essential, including surgical clipping. 3, 4 Here, we present an operative video demonstrating the surgical clip occlusion of previously ruptured middle cerebral artery and anterior communicating artery aneurysms that had been treated with the WEB device and had sizable recurrence on follow-up angiography. Informed consent was obtained from both patients. Lessons learned include the following: (1) the WEB device is highly compressible, unlike coils; (2) proximal WEB marker may interfere with clip closure; (3) no evidence of WEB extrusion into the subarachnoid space; (4) no more scarring than expected in ruptured cases; and (5) clipping is a feasible option for treating WEB recurrent or residual aneurysms.